2019
DOI: 10.1097/iae.0000000000001940
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Anatomical Significance of the Ectopic Inner Foveal Layers in Eyes With Idiopathic Epiretinal Membranes

Abstract: The presence of EIFL should be considered a negative prognostic factor for postoperative anatomical and functional recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
104
6
27

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(162 citation statements)
references
References 28 publications
13
104
6
27
Order By: Relevance
“…21 Other investigators have suggested that Muller cells are involved at the molecular level. 10 The analysis of vitreal cytokines in the current study revealed that CD163 and M-CSF were significantly higher in the EIFL group than they were in the non-EIFL group. Elevated M-CSF levels reflect macrophage differentiation.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…21 Other investigators have suggested that Muller cells are involved at the molecular level. 10 The analysis of vitreal cytokines in the current study revealed that CD163 and M-CSF were significantly higher in the EIFL group than they were in the non-EIFL group. Elevated M-CSF levels reflect macrophage differentiation.…”
Section: Discussionmentioning
confidence: 43%
“…[18][19][20] One of the most important recent findings associated with BCVA in ERM is EIFL. Govetto et al 8,10 demonstrated that the presence of EIFLs in ERMs is associated with significant vision loss in these eyes. It is also a negative prognostic factor for postoperative anatomic and functional recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…При этом величина эктопии внутренних слоев сетчатки рассчитывалась в микронах в центре фовеа по A. Govetto и соавт. [14,17] (рис. 1).…”
Section: материал и методыunclassified
“…В литературе показана зависимость визуальных исходов хирургического лечения ЭММ от отдельных предоперационных факторов: длительности заболевания, деформации внутренних слоев сетчатки, кистозного макулярного отека (КМО), состояния наружных слоев сетчатки, остроты зрения (ОЗ). Однако эти работы, как правило, анализируют влияние лишь одного-двух предикторов на функциональный результат удаления ЭММ [9][10][11], носят ретроспективный характер [9,[12][13][14][15] или ограничиваются короткими (до 6 мес) сроками послеоперационного наблюдения [12,13,16].…”
unclassified